St-N, a novel alkaline derivative of stevioside, reverses docetaxel resistance by targeting lysosomes in vitro and in vivo. - Yanxia Guo; Shikang Wang; Qun Liu; Yan Dong; Yongqing Liu (PLoS ONE)
Drug resistance of cancers remains a major obstacle due to limited therapeutics. Lysosome targeting is an effective method for overcoming drug resistance in cancer cells. St-N (ent-13-hydroxy-15-kaurene-19-acid N-methylpiperazine ethyl ester) is a novel alkaline stevioside derivative with an amine group. In this study, we found that docetaxel (Doc)-resistant prostate cancer (PCa) cells were sensitive to St-N. Mechanistically, the alkaline characteristic of St-N led to targeting lysosomes, as evidenced by lysosomal swelling and rupture through transmission electron microscopy and Lyso-tracker Red staining. St-N destabilized lysosomal membrane by impairing lysosomal membrane proteins and acid sphingomyelinase. As a result, St-N caused cathepsins to release from the lysosomes into the cytosol, eventually triggering apoptotic and necrotic cell death. Meanwhile, the cytoprotective role of lysosomal activation under docetaxel treatment was interrupted by St-N, leading to significant synergistic cytotoxicity of docetaxel and St-N. In docetaxel-resistant PCa homograft mice, St-N significantly inhibited the growth of RM-1/Doc homografts and enhanced the anticancer effects of docetaxel, but did not show significant toxicity. Taken together, these findings demonstrated that St-N reversed docetaxel resistance in vitro and in vivo by destabilizing lysosomal membranes to promote cell death, thus providing a strong rationale for applying St-N in docetaxel-resistant PCa.